The Effectiveness of Using Animated Storytelling Technique for Developing Speaking Skill - Amany A. Alsabbagh; Al-Shaimaa M. Al-Rashidy (International Journal of Instructional Technology and Educational Studies)
This study aims to address the persistent challenges faced by English as a Foreign Language (EFL) learners in developing their speaking skills. It introduces a novel program centered on animated storytelling through multimedia, designed to enhance the speaking proficiency of first-year secondary school students. To investigate the program's effectiveness, two classes were randomly assigned as an experimental group and a control group, each consisting of 30 students. The experimental group received training through the animated storytelling program, while the control group followed traditional instruction methods. The program encompassed 13 multimedia short stories.Pre and post-tests were administered to both groups to evaluate speaking skills in terms of fluency, accuracy, and comprehensibility. Statistical analysis, including t-tests, was employed to assess students' speaking performance. The results confirm the effectiveness of the animated storytelling program in enhancing the overall speaking skills of first-year secondary school students, including significant improvements in fluency, accuracy, and comprehensibility.The findings of this study offer compelling evidence regarding the effectiveness of the animated storytelling technique, implemented through the multimedia short stories program, in enhancing the overall speaking skills of first-year secondary school students. Notably, the program had a positive impact on all three crucial components of speaking: fluency, accuracy, and comprehensibility. These results underscore the potential of animated storytelling as a pedagogical tool for improving speaking skills within the educational context.